Prevalensi Kanker Kolorektal di RSUD Dr. Soedarso Pontianak Tahun 2018 - 2021 - Radisha Suci Maharani; Heru Fajar Trianto; Desriani Lestari (Universitas Muhammadiyah Manado, 2024)
The prevalence of colorectal cancer is increasing globally. Seven percent of all cancer cases in West Kalimantan in 2018-2020 were colorectal cancer which was mostly influenced by age, sex, and lifestyle factors, as well as genetic disorders. To determine the prevalence and frequency distribution of colorectal cancer based on age, gender, main symptom, supporting examination, stage of cancer, anatomical location of cancer, and management of patients. It was a descriptive study. The sample of this study were all patients with colorectal cancer in RSUD Dr. Soedarso Pontianak in 2018-2021 and fulfills the inclusion and exclusion criteria by using the total sampling technique. In this study, 109 samples were found. The frequency distribution of the highest case in 2019 was 35 cases (32.1%), the age range of patients was 56-63 years (23.9%), on male (54.1%), the main symptom was abdominal pain (50 ,5%), supporting examination was complete blood count (76.1%), stage III (29.4%), anatomical location in the rectum (33.9%), laparotomy (21.1%). The prevalence of colorectal cancer in Dr. Soedarso Hospital in 2018-2021 was 109 patients with the highest prevalence in 2019 was 32.1%.